PELAYANAN PUBLIK MASA PANDEMI COVID-19 DI KANTOR CAMAT KEMA KABUPATEN MINAHASA UTARA - IBRAHIM, MONICA APRILIA; PANGKEY, MASJE; DENGO, SALMIN (Sam Ratulangi University, 2021)
The purpose of this study was to find out how public services during the COVID-19 pandemic were at theKema sub-district office in North Minahasa Regency. The research method used in this research isdescriptive research with a qualitative approach. Data collection in this study was conducted throughinterviews, observation, and document collection. Meanwhile, the data analysis technique used in thisresearch is qualitative with Agus Dwiyanto's approach. The core problem of this research is that the serviceat the Kema sub-district office has not been maximized. Based on the results of the study, it can be concludedthat productivity in the Kema sub-district office is not optimal, it can be seen from employees who are notproductive at work and inadequate infrastructure. The quality of service in public services at the Kema subdistrictoffice has not been optimal, it can be seen from the inappropriateness and inaccuracy of theemployees. Responsiveness at the Kema sub-district office has not been optimal, it can be seen from theemployees who do not respond. The responsibility at the sub-district office is quite optimal, this can be fromclear procedures and service standards. Accountability at the Kema sub-district office has not been optimal,this can be seen from the lack of clear information on costs and service times.Keywords: Service, Public, covid-19